Fuel cell functional layer and activation method thereof
The method of preparing perovskite catalysts through the sol-gel method and precipitating Ni particles in situ solves the problem of carbon deposition when using methane, and improves the electrochemical performance and stability of the fuel cell.
Patent Information
- Application Number
- CN202411737170.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
Ni-based anodes are prone to carbon deposition when using hydrocarbon fuels such as methane, resulting in degradation of fuel cell performance and shortening of service life.
Perovskite-type catalysts were prepared by sol-gel method, and Ni particles were induced to be precipitated on the perovskite surface by hydrogen reduction and pretreatment to form high dispersion and stable Ni particles, which were used to improve the catalytic activity and stability of methane wet reforming hydrogen production reaction.
It significantly improves the electrochemical performance and stability of fuel cells when methane is used as fuel gas, extends the service life of the battery, simplifies the preparation process, and reduces costs.
Smart Images

Figure CN119627132A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of fuel cells, and in particular to a fuel cell functional layer and an activation method thereof. Background Art
[0002] Solid oxide fuel cell (SOFC) is an efficient and clean energy conversion device that can directly convert the chemical energy in the fuel into electrical energy, effectively alleviating problems such as energy crisis and environmental pollution. In particular, it can directly utilize hydrocarbons, a fuel with abundant reserves. Compared with the use of hydrogen fuel, the system operating cost is significantly reduced, the energy utilization efficiency is also improved, and it has huge economic benefits.
[0003] Currently, the most commonly used anode for SOFC is Ni-based. However, when hydrocarbon fuels such as methane are used directly, serious carbon deposition will occur on the Ni-based anode, causing the battery performance to degrade and the service life to be greatly shortened.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The purpose of the present disclosure is to provide a fuel cell functional layer and an activation method thereof, aiming to improve the electrochemical performance and stability of a carbon hydrogen fuel cell when methane is used as a fuel gas.
[0006] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.
[0007] According to one aspect of the present disclosure, a method for activating a functional layer of a fuel cell is provided, comprising: preparing a perovskite catalyst by a sol-gel method using a metal nitrate as a metal precursor, citric acid and ethylenediaminetetraacetic acid as a complexing agent, and ammonia water as a pH regulator; uniformly grinding a mixed solution of ethyl cellulose dissolved in pine alcohol and the perovskite catalyst to obtain an electrode slurry, and screen-printing the electrode slurry on a fuel cell to obtain an initial functional layer; subjecting the fuel cell to hydrogen reduction and pre-treating it with wet hydrogen or a mixture of wet hydrogen and diluted methane to induce the perovskite catalyst in the initial functional layer to form in-situ precipitated Ni particles to obtain an active functional layer.
[0008] Optionally, the method uses metal nitrate as a metal precursor, citric acid and ethylenediaminetetraacetic acid as complexing agents, and ammonia water as a pH regulator to prepare a perovskite catalyst by a sol-gel method, comprising: dissolving the metal precursor in deionized water to obtain a first mixed solution, and adding the complexing agent and the pH regulator to the first mixed solution to obtain a second mixed solution; stirring the second mixed solution evenly and then heating it to obtain a gel, and drying the gel to obtain a catalyst precursor; sintering the catalyst precursor at a high temperature to obtain the perovskite catalyst; the perovskite catalyst is LaNi 1-x Mn x O3.
[0009] Optionally, the molar ratio of the metal ion of the metal precursor, the citric acid and the ethylenediaminetetraacetic acid is 1:1:1-1:4:2; and the pH of the second mixed solution is 6-8.
[0010] Optionally, in the drying process, the drying temperature is 100-300° C. and the drying time is 10-20 hours.
[0011] Optionally, during the high-temperature sintering process, the sintering temperature is 900-1200° C., and the heating rate is 1-5° C. / min.
[0012] Optionally, the mass ratio of the ethyl cellulose to the terpineol is 3:97-6:94; the mass ratio of the mixed solution to the perovskite catalyst is 1:1-1.5:1.
[0013] Optionally, the process parameters of the screen printing are: the screen has a mesh size of 100-300, and the screen printing is performed 1-10 times; and the thickness of the initial functional layer is 10-200 μm.
[0014] Optionally, during the hydrogen reduction process, the temperature is 600°C-800°C, and the heating rate is 2-10°C / min.
[0015] Optionally, during the pretreatment process, the volume flow rate of the mixed gas is 50-1000 mL / min.
[0016] According to a second aspect of the present disclosure, a fuel cell functional layer is provided. The fuel cell functional layer is prepared by using the above-mentioned activation method for the fuel cell functional layer.
[0017] The exemplary embodiments of the present disclosure may have some or all of the following beneficial effects:
[0018] In the technical solutions provided in some embodiments of the present disclosure, the prepared perovskite catalyst is used to make the active functional layer of the fuel cell. On the one hand, compared with the catalyst prepared by the impregnation method, the metal Ni nanoparticles are induced to precipitate in situ from the perovskite surface after pretreatment with a mixed gas of methane and / or wet hydrogen, forming Ni particles with high dispersion and firmly bonded to the carrier, which greatly improves the catalytic activity and stability of the methane wet reforming hydrogen production reaction, which is much higher than the catalyst prepared by the impregnation method; on the other hand, the perovskite catalyst with anti-carbon deposition and anti-sintering stability is prepared by combining the sol-gel method, induced activation and other strategies, which simplifies the fuel cell preparation process, enhances the structural stability of the battery, and the raw materials are widely available, so that the entire preparation process is short in time, low in energy consumption and low in cost.
[0019] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0021] Figure 1 A schematic flow chart schematically illustrates a method for activating a fuel cell functional layer in an exemplary embodiment of the present disclosure;
[0022] Figure 2 Schematically showing the SEM images of the fuel cell prepared in exemplary embodiment 1 of the present disclosure before and after pretreatment;
[0023] Figure 3 The voltage of the fuel cell prepared in the exemplary embodiment 1 of the present disclosure at constant current is schematically shown;
[0024] Figure 4 Schematically showing an impedance diagram of a fuel cell prepared by exemplary embodiment 1 of the present disclosure;
[0025] Figure 5 A SEM image schematically showing the thickness of the active functional layer of the fuel cell prepared in exemplary embodiment 1 of the present disclosure;
[0026] Figure 6 The power density of a fuel cell in the prior art under pure H2 conditions is schematically shown;
[0027] Figure 7 The power density of the fuel cell prepared by the exemplary embodiment 1 of the present disclosure under pure H2 conditions is schematically shown;
[0028] Figure 8 Schematically showing the SEM images of the fuel cell prepared in Exemplary Embodiment 2 of the present disclosure before and after pretreatment;
[0029] Fig. 9 Schematically showing the voltage of the fuel cell prepared in Exemplary Embodiment 2 of the present disclosure at constant current;
[0030] Fig.10 Schematically showing an impedance diagram of a fuel cell prepared in exemplary embodiment 2 of the present disclosure;
[0031] Fig.11 Schematically showing the SEM images of the fuel cell prepared in Exemplary Embodiment 3 of the present disclosure before and after pretreatment;
[0032] Fig.12 Schematically showing the voltage of the fuel cell prepared in Exemplary Embodiment 3 of the present disclosure at constant current;
[0033] Fig.13 The impedance diagram of the fuel cell prepared in exemplary embodiment 3 of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0034] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.
[0035] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.
[0036] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.
[0037] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.
[0038] A carbon-hydrogen fuel cell is a battery that uses hydrocarbons as fuel and oxygen as an oxidant. Compared with hydrogen fuel cells, its fuel source is more extensive. For example, methane, methanol, ethane, etc. can all be used as fuel gas for power generation, reducing dependence on a single energy source.
[0039] Among them, solid oxide fuel cells (SOFCs) are efficient and clean energy conversion devices that can directly convert chemical energy in fuels into electrical energy, effectively alleviating energy crises and environmental pollution. In particular, they can directly utilize hydrocarbons, a fuel with abundant reserves. Compared with the use of hydrogen fuel, the system operating costs are significantly reduced, and the energy utilization efficiency is also improved, which has huge economic benefits. Currently, the most commonly used SOFC anode is Ni-based, but when hydrocarbon fuels such as methane are used directly, serious carbon deposition will occur on the Ni-based anode, causing the battery performance to deteriorate and the service life to be greatly shortened.
[0040] When methane (CH4) is used as SOFC fuel, it is often first reformed with an oxygen source (H2O, CO2, O2) to generate synthesis gas (H2 / CO), which is then provided to the SOFC as fuel. Therefore, how to make SOFC based on methane fuel generate electricity efficiently and stably is a major challenge in the commercialization of its technology. Compared with external reforming independent of the SOFC fuel reformer, internal reforming is to place the methane reforming process inside the SOFC cell, which has higher reforming efficiency and energy utilization efficiency, and greatly reduces the amount of air used on the cathode side. By developing an efficient reforming catalyst and adding it as a functional layer to the outside of the SOFC anode, the problem of anode carbon deposition when methane is the fuel gas can be solved, and the power generation life of the SOFC can be improved.
[0041] In the methane reforming hydrogen production reaction, Ni-based catalysts have been widely studied and applied due to their catalytic activity comparable to that of precious metals and their low price. However, the problem of easy carbon deposition and sintering of Ni-based catalysts at reaction temperatures (700-1100°C) remains the biggest challenge facing researchers. Therefore, developing new materials and studying the structure-activity relationship of Ni-based catalysts in the methane reforming hydrogen production reaction are of great significance and application value.
[0042] Studies have found that by reducing the size of the active component Ni particles, that is, increasing the dispersion of Ni, its anti-sintering performance can be effectively improved. Smaller Ni particles are not conducive to the nucleation and growth of carbon, and can also inhibit the formation of carbon deposits. In recent years, the in-situ precipitation method has attracted widespread attention to prepare highly dispersed and highly active Ni catalysts. This method places the active component Ni in an oxide precursor (perovskite, spinel, etc.), and after pretreatment steps such as reduction and activation, in-situ precipitation on the oxide surface forms Ni particles with high dispersion and firm bonding to the carrier. It has great potential in catalyzing methane reforming hydrogen production reactions.
[0043] Perovskite is a type of mixed metal oxide with high temperature stability and good anti-carbon deposition performance. It is usually represented by the general formula ABO3, where A is an alkaline earth metal or La series element, and B is mainly a transition metal. Among them, the A and B ions can be partially replaced by other metal ions to form a variety of cation-substituted perovskite materials (A 1-x A' x B 1-y B' y O3), this substitution will cause lattice defects, promote oxygen adsorption on the surface of perovskite catalysts, enhance the migration ability of lattice oxygen, and thus improve the catalyst activity.
[0044] Therefore, in view of the shortcomings of the prior art, the present invention adopts the sol-gel method to prepare the perovskite LaNi 1-x Mn x O3 catalyst precursor, through calcination and high temperature pretreatment to achieve LaNi 1-x Mn x O3-induced activation of the catalyst yields a perovskite-type LaNi with both high activity and high stability 1-x Mn x O3 catalyst is used as the functional layer of SOFC to achieve long-term and efficient power generation with methane as the fuel gas, solving the problem that Ni-based catalysts are prone to carbon deposition and sintering when methane is used as the fuel gas, resulting in a short SOFC life.
[0045] The implementation details of the technical solution of the embodiment of the present disclosure are elaborated in detail below.
[0046] Figure 1 The following is a schematic diagram of a method for activating a fuel cell functional layer in an exemplary embodiment of the present disclosure. Figure 1 As shown, the activation method of a fuel cell functional layer includes steps S101 to S105:
[0047] Step S101, using metal nitrate as a metal precursor, citric acid and ethylenediaminetetraacetic acid as complexing agents, and ammonia water as a pH regulator to prepare a perovskite catalyst by a sol-gel method;
[0048] Step S103, grinding a mixed solution of ethyl cellulose and pinene alcohol and the perovskite catalyst evenly to obtain an electrode slurry, and screen-printing the electrode slurry on a fuel cell to obtain an initial functional layer;
[0049] Step S105, the fuel cell is subjected to hydrogen reduction and pre-treated with wet hydrogen or a mixture of wet hydrogen and diluted methane to induce the perovskite catalyst in the initial functional layer to form in-situ precipitated Ni particles to obtain an active functional layer.
[0050] In the technical solutions provided in some embodiments of the present disclosure, the prepared perovskite catalyst is used to make the active functional layer of the fuel cell. On the one hand, compared with the catalyst prepared by the impregnation method, the metal Ni nanoparticles are induced to precipitate in situ from the perovskite surface after pretreatment with a mixed gas of methane and / or wet hydrogen, forming Ni particles that are precipitated in situ and firmly bonded to the carrier, which greatly improves the catalytic activity and stability of the methane wet reforming hydrogen production reaction, which is much higher than the catalyst prepared by the impregnation method; on the other hand, the perovskite catalyst with anti-carbon deposition and anti-sintering stability is prepared by combining the sol-gel method, induced activation and other strategies, which simplifies the fuel cell preparation process, enhances the structural stability of the battery, and the raw materials are widely available, so that the entire preparation process is short in time, low in energy consumption and low in cost.
[0051] Hereinafter, each step of the method for activating the functional layer of the fuel cell in this exemplary embodiment will be described in more detail with reference to the accompanying drawings and examples.
[0052] In step S101, a perovskite catalyst is prepared by a sol-gel method using metal nitrate as a metal precursor, citric acid and ethylenediaminetetraacetic acid as complexing agents, and ammonia water as a pH regulator;
[0053] In one embodiment of the present disclosure, the specific process of preparing the perovskite catalyst in step S101 includes: dissolving the metal precursor in deionized water to obtain a first mixed solution, and adding the complexing agent and the pH regulator to the first mixed solution to obtain a second mixed solution; stirring the second mixed solution evenly and heating it to obtain a gel, and drying the gel to obtain a catalyst precursor; sintering the catalyst precursor at a high temperature to obtain the perovskite catalyst; the perovskite catalyst is LaNi 1-x Mn x O3.
[0054] Specifically, firstly, materials are selected, metal nitrate is selected as a metal precursor, citric acid and ethylenediaminetetraacetic acid (EDTA) are selected as complexing agents, and ammonia water is selected as a pH regulator, and dissolved in deionized water to obtain a mixed solution. Among them, the metal nitrate is added in a molar ratio, and the molar ratio of the metal ion of the metal precursor, the citric acid and the ethylenediaminetetraacetic acid is 1:1:1-1:4:2. The pH value of the mixed solution is adjusted to 6-8 with ammonia water.
[0055] The mixed solution is then heated and stirred until a viscous gel is obtained, and then placed in an oven for drying to obtain a loose and porous catalyst precursor. Specifically, during the drying process, the drying temperature of the gel is 100-300° C., and the drying time is 10-20 hours.
[0056] Finally, sintering is performed to sinter the catalyst precursor at high temperature to obtain perovskite-type LaNi 1-x Mn x O3 catalyst. During the high temperature sintering process, the sintering temperature is 900-1200°C and the heating rate is 1-5°C / min.
[0057] In step S103, a mixed solution of ethyl cellulose dissolved in pinene alcohol and the perovskite catalyst are ground evenly to obtain an electrode slurry, and the electrode slurry is screen-printed on a fuel cell to obtain an initial functional layer.
[0058] The mass ratio of ethyl cellulose to pineol is 3:97-6:94; the mass ratio of the mixed solution to the perovskite catalyst is 1:1-1.5:1.
[0059] In one embodiment of the present disclosure, during screen printing, an initial functional layer with a thickness of 10-200 μm is obtained after 100-300 mesh screen printing is performed 1-10 times.
[0060] In step S105, the fuel cell is subjected to hydrogen reduction and pre-treated with wet hydrogen or a mixture of wet hydrogen and diluted methane to induce the perovskite catalyst in the initial functional layer to form in-situ precipitated Ni particles to obtain an active functional layer.
[0061] Specifically, during the hydrogen reduction process, the temperature is 600°C-800°C, and the heating rate is 2-10°C / min.
[0062] During pretreatment, wet hydrogen (H2O / H2) or a mixture of wet hydrogen and diluted methane (10% CH4 / 90% Ar) is used to obtain in-situ precipitated Ni particles for catalytic methane reforming to produce hydrogen, with a volume flow rate of 50-1000 mL / min.
[0063] Based on the above method, on the one hand, the highly catalytically active LaNi1-x Mn x O3 perovskite catalyst, through the screening of pretreatment conditions, induces the in-situ precipitation of metal Ni nanoparticles from the perovskite surface, forming Ni particles that are in-situ precipitated and firmly bonded to the carrier. Its catalytic activity, stability and electrochemical performance for methane wet reforming hydrogen production reaction are much higher than those of catalysts prepared by impregnation method and traditional NiLa / Al2O3 catalysts.
[0064] On the other hand, LaNi with anti-carbon deposition and anti-sintering stability in methane reforming hydrogen production reaction was obtained by combining sol-gel method, induced activation and other strategies. 1-x Mn x O3 perovskite catalyst is used to improve the electrochemical performance and long-term stability of the battery when methane is used as the fuel gas. It simplifies the fuel cell preparation process, has a simple process, and the structure and catalytic performance of the prepared perovskite catalyst are controllable. The raw materials involved are widely available and inexpensive, the preparation process is low-cost, has a wide range of applications, is easy to implement, and the entire preparation process is short in time and low in energy consumption, making it suitable for industrial mass production.
[0065] The present invention will be further described below according to specific embodiments:
[0066] Example 1
[0067] This embodiment includes the following steps:
[0068] Step 1, material selection: select lanthanum nitrate, nickel nitrate, and manganese nitrate hydrate (molar ratio of 1:0.2:0.8) in a stoichiometric ratio as metal precursors, dissolve them in an appropriate amount of deionized water, add citric acid and ethylenediaminetetraacetic acid in a stoichiometric ratio as complexing agents, and use ammonia water as a pH regulator to adjust the pH of the mixed solution to 7, heat and stir the solution until a viscous gel is obtained, and dry it in an oven at 200° C. to obtain a loose and porous catalyst precursor, wherein the molar ratio of metal ions, citric acid, and ethylenediaminetetraacetic acid in the metal precursor is 1:4:2;
[0069] Step 2: Sintering: The catalyst precursor obtained in step 1 is sintered at 1000°C in a muffle furnace to obtain a perovskite LaNi 0.2 Mn 0.8 O3 catalyst. The sintering process is to increase the temperature to 600℃ at 1℃ / min, keep it at that temperature for 1 hour, then increase the temperature to 1000℃ at 2℃ / min, keep it at that temperature for 5 hours, and then end the process. 0.2 Mn 0.8 The crystal structure of O3 catalyst was confirmed by XRD.
[0070] Step 3, screen printing: The perovskite LaNi 0.2 Mn0.8 The O3 catalyst was dissolved in a pine alcohol mixed solution with 4 wt.% ethyl cellulose at a ratio of 1.2:1 and ground evenly, and then printed on a button cell through a 300-mesh screen to obtain a SOFC with a functional layer and a thickness of about 20 μm.
[0071] Step 4, pretreatment: The button cell obtained in step 3 is reduced and pretreated in situ. First, it is reduced in a hydrogen atmosphere at a temperature of 800°C and a heating rate of 5°C / min. Then it is pretreated at 800°C under the conditions of 200ml / min 3% H2O / H2 or 100ml / min 3% H2O / H2 and 100ml / min 10% CH4 / 90% Ar mixed gas to obtain in situ precipitated Ni particles for catalytic methane reforming to produce hydrogen.
[0072] Step 5: Electrochemical performance test: Switch to methane fuel gas and test the battery open circuit voltage, power density, ohmic impedance and long-term stability. The SOFC test conditions with methane as fuel gas are 200ml / min 3% H2O / 10% CH4 / 87% Ar, and the test temperature is 800℃.
[0073] Figure 2 The SEM images of the fuel cell prepared in Exemplary Embodiment 1 of the present disclosure before and after pretreatment are schematically shown. Figure 2 (a) is the SEM image before treatment. Figure 2 (b) is the SEM image after treatment.
[0074] Figure 2 (a) and Figure 2 (b) By comparison, it can be clearly seen that after pretreatment, in-situ precipitated and highly dispersed Ni particles grow on the surface of the perovskite.
[0075] Figure 3 The voltage of the fuel cell prepared in the exemplary embodiment 1 of the present disclosure at constant current is schematically shown. Figure 3 As shown in the figure, when the current is 0.8A, the output voltage of the battery is basically stable at about 0.8V within 48 hours of the test, indicating that the addition of LaNi 0.2 Mn 0.8 The fuel cell with O3 functional layer also has excellent electrochemical performance and stability in methane fuel gas.
[0076] Figure 4 The impedance diagram of the fuel cell prepared by the exemplary embodiment 1 of the present disclosure is schematically shown. Figure 4 As shown, LaNi is added 0.2 Mn 0.8 The ohmic impedance of the fuel cell with O3 functional layer (R Ω ) is 0.20Ω / cm 2 , polarization impedance (RP ) is 0.088Ω / cm 2 , indicating its excellent electrochemical performance.
[0077] Figure 5 The SEM image schematically shows the thickness of the active functional layer prepared in exemplary embodiment 1 of the present disclosure.
[0078] Figure 6 The power density of a fuel cell in the prior art under pure H2 conditions is schematically shown, that is, a blank fuel cell without a functional layer. At this time, the power density of the battery is 0.97 W / cm 2 . Figure 7 The power density of the fuel cell prepared by the exemplary embodiment 1 of the present disclosure under pure H2 conditions is schematically shown to be 1.53 W / cm 2 .pass Figure 6 and Figure 7 By comparison, the addition of the functional layer can also improve the power density of the fuel cell under pure H2 conditions, indicating that the in-situ precipitated Ni particles can not only catalyze the methane reforming hydrogen production reaction, but also help improve the electrochemical performance of the battery under pure H2 conditions.
[0079] Example 2
[0080] This embodiment includes the following steps:
[0081] Step 1, material selection: select lanthanum nitrate, nickel nitrate, and manganese nitrate hydrate (molar ratio of 1:0.5:0.5) in a stoichiometric ratio as metal precursors, dissolve them in an appropriate amount of deionized water, add citric acid and ethylenediaminetetraacetic acid in a stoichiometric ratio as complexing agents, and use ammonia water as a pH regulator to adjust the pH of the mixed solution to 6, heat and stir the solution until a viscous gel is obtained, and dry it in an oven at 100° C. to obtain a loose and porous catalyst precursor, wherein the molar ratio of metal ions, citric acid, and ethylenediaminetetraacetic acid in the metal precursor is 1:1:1;
[0082] Step 2: Sintering: The catalyst precursor obtained in step 1 is sintered at 1200°C in a muffle furnace to obtain a perovskite LaNi 0.2 Mn 0.8 O3 catalyst. The sintering process is to increase the temperature to 600℃ at 1℃ / min, keep it at that temperature for 1 hour, then increase the temperature to 1200℃ at 5℃ / min, keep it at that temperature for 5 hours, and then end the process. 0.2 Mn 0.8 The crystal structure of O3 catalyst was confirmed by XRD.
[0083] Step 3, screen printing: The perovskite LaNi 0.2 Mn 0.8The O3 catalyst was dissolved in a pine alcohol mixed solution with 6 wt.% ethyl cellulose at a ratio of 1.5:1 and ground evenly, and the mixture was screen-printed on a button cell with a mesh size of 250 to obtain a SOFC with a functional layer.
[0084] Step 4, pretreatment: The button cell obtained in step 3 is reduced and pretreated in situ. First, it is reduced in a hydrogen atmosphere at a temperature of 700°C and a heating rate of 2°C / min. Then it is pretreated at 800°C under the conditions of 500ml / min 3% H2O / H2 or 50ml / min 3% H2O / H2 and 50ml / min 10% CH4 / 90% Ar mixed gas to obtain in situ precipitated Ni particles for catalytic methane reforming to produce hydrogen.
[0085] Step 5: Electrochemical performance test: Switch to methane fuel gas and test the battery open circuit voltage, power density, ohmic impedance and long-term stability. The SOFC test conditions with methane as fuel gas are 200ml / min 3% H2O / 10% CH4 / 87% Ar, and the test temperature is 800℃.
[0086] Figure 8 The SEM images of the fuel cell prepared in Exemplary Embodiment 2 of the present disclosure before and after pretreatment are schematically shown. Figure 8 (a) is the SEM image before treatment. Figure 8 (b) is the SEM image after treatment.
[0087] Figure 8 (a) and Figure 8 (b) By comparison, it can be clearly seen that highly dispersed Ni particles with a certain particle size are precipitated in situ on the perovskite surface.
[0088] Fig. 9 The voltage of the fuel cell prepared in Example 2 of the present disclosure at constant current is schematically shown. Fig. 9 As shown in the figure, when the current is 0.6A, the output voltage of the battery is basically stable at about 0.75V within 48 hours of the test, indicating that the addition of LaNi 0.5 Mn 0.5 The fuel cell with O3 functional layer also has good stability and good electrochemical performance in methane fuel gas, but it is slightly lower than that in Example 1.
[0089] Fig.10 The impedance diagram of the fuel cell prepared by the exemplary embodiment 2 of the present disclosure is schematically shown. Fig.10 As shown, LaNi is added 0.5 Mn 0.5 The ohmic impedance of the fuel cell with O3 functional layer (R Ω ) is 0.31Ω / cm 2 , polarization impedance (R P) is 0.43Ω / cm 2 , indicating that its electrochemical performance is good, but not as good as Example 1, indicating that the relatively large Ni particles in this example are not conducive to improving the electrochemical performance of the fuel cell.
[0090] Example 3
[0091] This embodiment includes the following steps:
[0092] Step 1, material selection: select lanthanum nitrate and nickel nitrate hydrate (molar ratio of 1:1) in a stoichiometric ratio as metal precursors, dissolve them in an appropriate amount of deionized water, add citric acid and ethylenediaminetetraacetic acid in a stoichiometric ratio as complexing agents, and use ammonia water as a regulator to adjust the pH to 8, heat and stir the solution until a viscous gel is obtained, and dry it in an oven at 300° C. to obtain a loose and porous catalyst precursor, wherein the molar ratio of metal ions, citric acid and ethylenediaminetetraacetic acid in the metal precursor is 1:1:1;
[0093] Step 2, sintering: The catalyst precursor obtained in step 1 is sintered at 900°C in a muffle furnace to obtain a perovskite LaNiO3 catalyst. The sintering process is to increase the temperature to 600°C at 1°C / min, keep it for 1 hour, then increase the temperature to 900°C at 2°C / min, keep it for 5 hours, and then end the procedure. The crystal structure of the obtained perovskite LaNiO3 catalyst is confirmed by XRD.
[0094] Step 3, screen printing: the perovskite LaNiO3 catalyst obtained in step 2 is mixed with 3wt.% ethyl cellulose in a pine alcohol mixed solution at a ratio of 1:1 and ground evenly, and then printed on a button cell through a 100-mesh screen to obtain a SOFC with a functional layer.
[0095] Step 4, pretreatment: The button cell obtained in step 3 is reduced and pretreated in situ. First, it is reduced in a hydrogen atmosphere at a temperature of 600°C and a heating rate of 10°C / min. Then it is pretreated at 800°C under the conditions of 500ml / min 3% H2O / H2 or 500ml / min 3% H2O / H2 and 500ml / min 10% CH4 / 90% Ar mixed gas to obtain in situ precipitated Ni particles for catalytic methane reforming to produce hydrogen.
[0096] Step 5: Electrochemical performance test: Switch to methane fuel gas and test the battery open circuit voltage, power density, ohmic impedance and long-term stability. The SOFC test conditions with methane as fuel gas are 200ml / min 3% H2O / 10% CH4 / 87% Ar, and the test temperature is 800℃.
[0097] Fig.11The SEM images of the fuel cell prepared in Exemplary Embodiment 3 of the present disclosure before and after pretreatment are schematically shown. Fig.11 (a) is the SEM image before treatment. Fig.11 (b) is the SEM image after treatment. Fig.11 (a) and Fig.11 (b) By comparison, it can be clearly seen that there are highly dispersed Ni particles precipitated in situ on the catalyst surface, but the size distribution is uneven, with both finely dispersed Ni particles and agglomerated Ni particles.
[0098] Fig.12 The voltage of the fuel cell prepared in the exemplary embodiment 3 of the present disclosure at constant current is schematically shown. Fig.12 As shown, when the current is 0.6A, the output voltage of the battery fluctuates between 0.25-0.45V within 48 hours of the test, indicating that the electrochemical performance and stability of the fuel cell with the LaNiO3 functional layer added in methane fuel gas are not as good as other perovskite catalysts doped with Mn elements.
[0099] Fig.13 The impedance diagram of the fuel cell prepared by the exemplary embodiment 3 of the present disclosure is schematically shown. Fig.13 As shown, the ohmic impedance (R Ω ) is 0.59Ω / cm 2 , polarization impedance (R P ) is 1.14Ω / cm 2 At this time, the impedance of the battery is significantly higher than that of Examples 1 and 2, indicating that slight carbon deposition or sintering may have occurred in the functional layer.
[0100] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.
[0101] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for activating a fuel cell functional layer, characterized in that: include: The perovskite catalyst was prepared by a sol-gel method using metal nitrate as metal precursor, citric acid and ethylenediaminetetraacetic acid as complexing agents, and ammonia as pH regulator. Grinding a mixed solution of ethyl cellulose and pinene alcohol and the perovskite catalyst uniformly to obtain an electrode slurry, and screen-printing the electrode slurry on a fuel cell to obtain an initial functional layer; The fuel cell is subjected to hydrogen reduction and pre-treated with wet hydrogen or a mixed gas of wet hydrogen and diluted methane to induce the perovskite catalyst in the initial functional layer to form in-situ precipitated Ni particles to obtain an active functional layer.
2. The method for activating a fuel cell functional layer according to claim 1, characterized in that: The method uses metal nitrate as a metal precursor, citric acid and ethylenediaminetetraacetic acid as complexing agents, and ammonia water as a pH regulator to prepare a perovskite catalyst through a sol-gel method, comprising: Dissolving the metal precursor in deionized water to obtain a first mixed solution, and adding the complexing agent and the pH regulator to the first mixed solution to obtain a second mixed solution; The second mixed solution is stirred evenly and then heated to obtain a gel, and the gel is dried to obtain a catalyst precursor; The catalyst precursor is subjected to high temperature sintering to obtain the perovskite catalyst; the perovskite catalyst is LaNi 1-x Mn x O3.
3. The method for activating a fuel cell functional layer according to claim 2, characterized in that: The molar ratio of the metal ion of the metal precursor, the citric acid and the ethylenediaminetetraacetic acid is 1:1:1-1:4:2; and the pH of the second mixed solution is 6-8.
4. The method for activating a fuel cell functional layer according to claim 2, characterized in that: In the drying process, the drying temperature is 100-300° C. and the drying time is 10-20 hours.
5. The method for activating a fuel cell functional layer according to claim 2, characterized in that: In the high temperature sintering process, the sintering temperature is 900-1200° C., and the heating rate is 1-5° C. / min.
6. The method for activating a fuel cell functional layer according to claim 1, characterized in that: The mass ratio of the ethyl cellulose to the terpineol is 3:97-6:94; the mass ratio of the mixed solution to the perovskite catalyst is 1:1-1.5:
1.
7. The method for activating a fuel cell functional layer according to claim 1, characterized in that: The process parameters of the screen printing are: the screen has 100-300 meshes, and the screen printing is performed 1-10 times; the thickness of the initial functional layer is 10-200 μm.
8. The method for activating a fuel cell functional layer according to claim 1, characterized in that: During the hydrogen reduction process, the temperature is 600°C-800°C, and the heating rate is 2-10°C / min.
9. The method for activating a fuel cell functional layer according to claim 1, characterized in that: During the pretreatment process, the volume flow rate was 50-1000 mL / min.
10. A fuel cell functional layer, characterized in that: The fuel cell functional layer is obtained by using the activation method for a fuel cell functional layer as described in claims 1 to 9 above.